Who was Steve Irwin? - Anastasio, Dina.; Eldridge, Jim (New York, Grosset & Dunlap, 2015)
Describes the life and career of Steve Irwin, famously known as the Crocodile Hunter, from his childhood and early love of animals to his rise in popularity as a film and television star and naturalist. --
Includes bibliographical references (p. 104-105).
690L
3-6
5.7
Keywords: Irwin, Steve, -- 1962-2006 -- Juvenile literature; Irwin, Steve, -- 1962-2006.; Herpetologists -- Australia -- Biography -- Juvenile literature; Naturalists -- Australia -- Biography -- Juvenile literature; Picture books; Herpetologists; Naturalists; Picture books; Herpetologists -- Biography; Naturalists -- Biography; Australia; Australia -- Biography; Biography; Juvenile works